2008
DOI: 10.1111/j.1365-2648.2007.04581.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of perioperative dialogues with children undergoing day surgery

Abstract: The perioperative dialogue used in our study, if translated into clinical practice, might therefore minimize distress and prepare children for the 'unknown' stressor that hospital care often presents. Further research is needed to compare anxiety and stress levels in children undergoing day surgery involving the perioperative dialogue and those having 'traditional' anaesthetic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 33 publications
1
55
1
1
Order By: Relevance
“…Yet, in support of other studies Lambert et al 349 (e.g. Boylan, 2004;Fortier et al, 2009;Garth and Aroni, 2003;Gibson, 2005;Wennstrom et al, 2008), a small number of the child participants in this study preferred not to be informed. As Lewis et al (2007) reported, sometimes children want their parents to protect them and are happy when communication is directed to parents because of the fear of hearing bad news or distressing information.…”
supporting
confidence: 83%
“…Yet, in support of other studies Lambert et al 349 (e.g. Boylan, 2004;Fortier et al, 2009;Garth and Aroni, 2003;Gibson, 2005;Wennstrom et al, 2008), a small number of the child participants in this study preferred not to be informed. As Lewis et al (2007) reported, sometimes children want their parents to protect them and are happy when communication is directed to parents because of the fear of hearing bad news or distressing information.…”
supporting
confidence: 83%
“…Resorting to the nurse, 12 receiving information, 4,16 play 25,28 and positive visual images 14 have previously been shown to alleviate the fear of young children. Moreover, expressing fear, rejecting and denying it are known to alleviate fears and pain in children 41 . Several coping strategies, for example, playing and crying, may probably act both as an expression of fear and a coping strategy, a fact that has also been noted previously 42 …”
Section: Discussionmentioning
confidence: 70%
“…Fear and anxiety are common feelings for patients who undergo surgery. Wennström, Hallberg, and Bergh (2008) explored what it meant for 6‐ to 9‐year‐old children to be hospitalized for day surgery, and found that the main concern for these children was that they were put into an unknown, unpredictable, and distressful situation, which had to be endured. The provision of adequate preparatory information to children is thus crucial and beneficial in helping them develop realistic expectations for the procedure and prevent distress from medical procedures (Kolk et al., 2000); lessening their anxiety and fear (Kain et al., 1996); increasing trust between the child, parents, and healthcare providers; and enhancing children's cooperation during a procedure.…”
Section: Literature Reviewmentioning
confidence: 99%